Temperature Significantly Regulates Gene Expressions of Vertebrae Chondrocytes and Osteoblasts in Juvenile Golden Pompano (Trachinotus ovatus) - Han, Mingyang; Fu, Zhengyi; Yang, Rui; Qin, Jian G.; Ma, Zhenhua (Frontiers in Marine Science, 2021)
To elucidate the possible molecular reaction of vertebral fusion in juvenile golden pompano at high temperature, we examined the changes in growth, vertebral fusion incidence, histological differences and transcription levels of genes related to bone development in juvenile golden pompano at 27 and 33°C for 30 days, respectively. The growth rate of juvenile fish was faster when the water temperature was 33°C, but the incidence of vertebral fusion was higher. Prolonged high water temperature reduced the osteogenic layer in the growth zone of the vertebral endplate and the elastic externa. The endplate growth areas of the fused vertebrae were transformed into cartilage tissue, which was then remodeled into bone. The intervertebral notochord tissue was transformed into bone and the intervertebral space disappeared. In normal phenotypes of vertebrae, short-term high temperature could promote the expression of genes related to cartilage differentiation and maturation, as well as genes related to osteoblastic differentiation. With the increase of culture time, the expression of genes related to cartilage and osteogenesis development was inhibited. In fused vertebrae, cartilage proliferation was enhanced, osteogenic differentiation was inhibited, and matrix mineralization may be enhanced. Genes associated with the development of chondrocytes and osteoblasts in the vertebrae of juvenile Trachinotus ovatus were significantly regulated by temperature and time. The results may contribute to further understanding of the occurrence of vertebral fusion at high temperature.